Analisis Diskriminan Tingkat Kecukupan Konsumsi Protein - Ardiana Priharwanti (Universitas Pekalongan, 2013)
Background: The frequency of food consumption in poor households are generally still low as was the case in the District of Kutai, East Kalimantan. District known as a wealthy district, but many have poor people, especially rural areas that rely only by eating a day. The low frequency of eating correlates with the incidence of malnutrition, as happened in the city of Bogor. Based on data from the Bogor City Health Department, during 2005 there were 240 children under five suffer from malnutrition, including marasmus status of 35 infants, five toddlers to marasmus kwarsiorkor and one tested positive for malnutrition. A variety of nutrition issues, as was the case-Protein Energy Malnutrition monitoring the consumption of protein has not been touched, so there is no indicator to see and determine the adequacy of protein intake. Until now there is no measurement that is easier to determine the adequacy of the level of protein consumption. Therefore, research on indicators of adequacy levels of protein consumption is still very necessary.Method: Research design was cross sectional, observational variables influence and be influenced to do well at one time. The study was conducted in April to November 2006. The study was conducted in rural and urban areas. Rural areas are represented by Sukamaju Village, District Cibungbulang Bogor and urban districts represented by the Official Village District Land Like Cereal City Bogor West Java province. Data collected includes primary data and secondary data. Discriminant analysis is used to mengkelaskan families into groups of less and consume enough protein based food consumption variables. Furthermore, to determine the adequacy of the level of protein intake according to household food consumption variables through discriminant analysis using the following method: suppose x is a vector of variables measuring household food consumption is p × 1 is spread according to the multivariate normal f1 (x) for the family enough protein consumption, which has a variance-covariance matrix equal the Σ1 = Σ2 = Σ and differ only vector average of μ1, μ2 because:f1 (x) =[(2π)1/2 I ∑I 1/2 ]-1 exp [(-1/2)(x- μ1)’ ∑-1 (x- μ1)]f2 (x) =[(2π)1/2 I ∑I 1/2 ]-1 exp [(-1/2)(x- μ2)’ ∑-1 (x- μ2)]Because the parameters Σ, μ1, and μ2 is unknown then the parameters of each alleged by S, x1, x2 with a note: S = (n1-1) S1 + (n2-1) S2Result: The prevalence of families with low levels of protein intake as much as 41.7%. Characteristics of families with low levels of protein consumption is as follows: the number of family members of 5-6 people, family head age 24-70 years, 23-60 years of maternal age, education level of head of household 0-12 years, and maternal education levels ranged between 0 up to 9 years. Ranked first single variable frequency of food consumption can be recommended as an indicator of the level of protein consumption is potatoes, with a discriminant equation,Y1 (X) = -0.02918 + 0.02026 XY2 (X) = -0.41907 + 0.07679 Xwhereas the two variables is the frequency of food consumption of potatoes and vegetables, with the discriminant equationY1 (X) = -0.73180 - 0.02342 0.01685 X1 + X2Y2 (X) = -1.46652 + 0.02346 X1 + 0.02058 X2.Keyword: discriminant analysis, consumption adequacy level protein